Empirical Evidence for Energy Efficiency Using Intermittent Gliding Flight in Northern Bald Ibises - Mizrahy-Rewald, Ortal; Perinot, Elisa; Fritz, Johannes; Vyssotski, Alexei L.; Fusani, Leonida; Voelkl, Bernhard; Ruf, Thomas (Frontiers in Ecology and Evolution, 2022)
Birds face exceptionally high energy demands during their flight. One visible feature of some species is alternating between flapping and gliding, which should allow them to save energy. To date, there is no empirical evidence of an energetic benefit to this. To understand the physiology behind the strategy, we equipped hand-raised Northern Bald Ibises (Geronticus eremita) with data loggers during human-guided migration. We monitored the position of the birds, wingbeats, overall dynamic body acceleration (ODBA) and heart rates as a proxy for energy expenditure. The energy expenditure was significantly affected by the length of flapping and gliding bouts. A pronounced decrease in heart rate was measured after already one second of gliding. Additionally, the heart rate at flapping bouts up to 30 seconds increased steadily but stabilized thereafter. The gilding proportion during intermittent flight affected the energy saving compared to continuous flapping. At a gliding proportion of about 20%, we measured a maximum of 11% saving based on heart rate measurement. At higher gliding proportions, the additional energy saving was negligible. Furthermore, as during flight not all energy is used for mechanical work, we found a greater decrease rate of ODBA at different gliding proportions compared to heart rate. Nevertheless, the combination of the two methods is essential to determine birds' movement and energy expenditure. This study provides empirical evidence that intermittent flight is energetically beneficial and can reduce the high costs of flights.